Describing correct UAVs cooperation architectures applied on an anti-terrorism scenario. (May 2021) - Gassara, Amal; Bouassida Rodriguez, Ismael
Abstract: In this paper, we propose a solution supporting the correct description of UAVs cooperation architectures and their reconfigurations. This solution is based on a graph transformation system that defines rules for changing UAVs cooperation architecture while being in conformance to an architectural style. An architecture instance is considered correct, if its corresponding graph can be generated by a sequence of rules. To be illustrated, our approach is applied on the SuperSenS project where UAVs have to cooperate during search-and-rescue mission. The UAVs system is used for the surveillance of closed military zones aiming at detecting terrorists and tracking them.